1991
DOI: 10.1002/ajmg.1320400111
|View full text |Cite
|
Sign up to set email alerts
|

Inversion‐duplication of bands q13→q21 of human chromosome 9

Abstract: Structural abnormalities involving heterochromatic regions of the human genome are difficult to characterize because these segments are G-band negative by GTG technique, a routinely used procedure in clinical cytogenetic laboratories. Chromosome abnormalities of such cases have gone undetected or were incorrectly characterized because these regions are so-called heteromorphisms or variants. Consequently, much anxiety has been aroused by the confusion between a chromosome abnormality and a normal heteromorphic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 23 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…One case did suggest slight mental retardation associated with duplication of 9q 13 ->q21 (Luke et al, 1991). However, the father was unavailable for cytogenetic analysis, and a de novo origin of this chromosome could not be established.…”
Section: Resultsmentioning
confidence: 99%
“…One case did suggest slight mental retardation associated with duplication of 9q 13 ->q21 (Luke et al, 1991). However, the father was unavailable for cytogenetic analysis, and a de novo origin of this chromosome could not be established.…”
Section: Resultsmentioning
confidence: 99%
“…In the present family, however, and also in a number of previously reported families [Sutherland and Eyre, 1981;Silengo et al, 1982;Jalal et al, 1990;Luke et al, 1991], the origin of mental retardation and/or dysmorphism in the index patient remains obscure, since no additional chromosomal abnormality could be detected.…”
Section: Discussionmentioning
confidence: 49%
“…Early studies using conventional techniques (C-R-GBanding) depicted this region as a homogeneously stained heterochromatic region [Jacobs, 1977;Babu et al, 1988], and attempts to evaluate the contents and the extent of the actual change behind either the variations in size and position [Berg et al, 1980;Docherty and Hultén, 1985;Knight et al, 1993] or the presence of unusual extra bands [Madan, 1978;Berg et al, 1980;Docherty and Hultén, 1985;Spedicato et al, 1985;Luke et al, 1991;Roland et al, 1992;Macera et al, 1995] have long been the subject of scrutiny and continual debate. Molecular cytogenetic techniques have now unequivocally shown that the region including the centromere and the secondary constriction of the normal chromosome 9 is mainly composed of three spatially distinct and specifically ranged domains of repeated satellite DNA sequences, namely, alpha, beta, and classical satellite III DNA [Singer, 1982;Hulsebos et al, 1988;Waye and Willars, 1989;Choo et al, 1991;Rocchi et al, 1991;Luke et al, 1992;Cook and Karpen, 1994;Haaf and Ward, 1994;Ramesh and Verma, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of relationship between heteromorphisms and early recurrent abortions was confirmed by Del Porto et al [16]. However, apparently common chromosomal variants, like those involving the heterochromatic region of chromosome 9, have to be checked carefully to avoid the existence of a complex rearrangement, especially when the carrier exhibits an abnormal phenotype [17].…”
Section: Discussionmentioning
confidence: 87%